SPECIALISED COMMUNICATION: A GENRE- BASED ANALYSIS AND STRATEGIES IN PRESIDENTIAL ELECTION PETITION TRIBUNAL JUDGMENTS BY THE SUPREME COURT OF NIGERIA - Agbeleoba, Samuel Oyeyemi; Feyisara, Olaitan Eunice; Akanle, Kemisola (International Journal of Research -GRANTHAALAYAH, 2025)
This study examines the specialized communication patterns in Nigerian Presidential Election Petition Tribunal judgments through a genre-based analysis framework. Using Halliday’s Generic Structure Pattern (GSP) as the theoretical foundation, the research analyzes the linguistic features, rhetorical strategies, and structural elements that characterize this specialized legal discourse. The study focuses on the 2023 Presidential Election Petition cases, particularly the Supreme Court judgment in Atiku v. INEC (No. 2) [2023] 19 NWLR, to identify recurring patterns and develop a comprehensive GSP equation for this genre. The ﬁndings reveal a systematic structure comprising both obligatory and optional elements that serve speciﬁc communicative functions within the Nigerian legal system. This research contributes to the understanding of legal discourse in post-colonial contexts and provides insights into how specialized communication operates within institutional frameworks.